Study of the electrical and thermal conductivity of compounds and solid solutions resulting from the study of the triple system (BaCl2-CuSO4-Na2CO3) - Saleh, Wajde Essa; Deep, Mohammed (Journal of natural sciences, life and applied sciences, 2021)
In this research, the electrical and thermal conductivity of the compounds BaCl2-CuSO4-Na2CO3 - Ba6Na8C4Cl12O12 - Ba6Cu4S4Cl12O16 - Cu6Na8S6C4O36 and the solid solutions resulting from the interaction of these compounds with each other, using the thermal conductivity measuring device (ITP-M64) and electrical conductivity measurement device (the four paths) were studied. The results are different between superconducting materials and medium conductive materials (semiconductors).
Keywords: phase diagram; solid solution; thermal conductivity; crystalline compounds; electrical conductivity; equilibrium phases